1979
DOI: 10.1213/00000539-197903000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Lidocaine to Trigger Porcine Malignant Hyperthermia

Abstract: Lidocaine, considered by some to be potentially dangerous in malignant hyperthermia (MH), was administered intravenously to a dose of 15 mg/kg to five conscious MH-susceptible pigs. Subsequently the same pigs were given 24 mg/kg intravenously over a period of 2 hours after being anesthetized with thiopental. All animals developed systemic toxicity to lidocaine but without evidence of MH. Prior administration of lidocaine did not prevent development of subsequent MH due to succinylcholine and halothane. Lidocai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Lidocaine-induced hyperthermia has been reported in a case where it was injected directly into the skeletal muscle and the local anesthetics were myotoxic. 3 Myofibril hypercontraction progresses to lytic degeneration, edema, and necrosis. Because lidocaine and bupivacaine were previously used twice in the present patient without any adverse events, these drugs are unlikely to have triggered the hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine-induced hyperthermia has been reported in a case where it was injected directly into the skeletal muscle and the local anesthetics were myotoxic. 3 Myofibril hypercontraction progresses to lytic degeneration, edema, and necrosis. Because lidocaine and bupivacaine were previously used twice in the present patient without any adverse events, these drugs are unlikely to have triggered the hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…In experiments with MH-susceptible pigs, infusion of amide local anaesthetics (lidocaine and bupivacaine) failed to produce overt MH, although high peak plasma levels exceeding the toxic concentration in humans were reached (8,9). One clinical report even describes the successful treatment of arrhythmias with lidocaine during M H (10).…”
Section: Discussionmentioning
confidence: 99%
“…Amide local anesthetics were previously thought to be harmful, because lidocaine may enhance in vitro contracture by inhibition of calcium sequestration into the sarcoplasmic reticulum. Reexamination has shown that lidocaine does not trigger MH in susceptible swine, even when given in doses above the convulsive threshold [100]. All local anesthetics, including the amides, are currently considered acceptable for anesthetic purposes [101,102].…”
Section: Non-anesthetic Drugs and Circumstancesmentioning
confidence: 99%